Addressing Cellulose Acetate Microfilm from a British Library perspective - Shenton, Helen (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2005)
This paper is about cellulose acetate microfilm from the British Library perspective. It traces how acetate microfilm became an issue for the British Library and describes cellulose acetate deterioration. This is followed by details of what has already been done about the situation and what action is planned for the future.